Productivity and profitability of improved versus existing cropping pattern in Kushtia region - Rahman, MS; Islam, MT; Prodhan, MZH; Hasan, MK; Khan, ASMMR (Bangladesh Journal of Agricultural Research, 2018)
The trial was conducted at Multi Location Testing (MLT) site under On-Farm Research Division, BARI, Kushtia during the last week of February, 2015 to second week of February, 2017 at farmers’ field condition to cover two cropping cycle of four crops. The main objectives of the trial were to verify the feasibility of growing improved cropping pattern Mustard-Mungbean-T.Aus-T.Aman rice and to compare its productivity and profitability with existing cropping pattern Lentil-Sesame-T.Aman rice. The varieties BARI Sarisha-15, BARI Mung-6, BRRI dhan48 and Binadhan-7 were used for the crop Mustard, Mungbean, T.Aus and T.Aman rice, respectively in the improved cropping pattern, while in case of existing pattern, the varieties were BARI Masur-6, BARI Till-3 and Binadhan-7 for Lentil, Sesame and T.Aman rice, respectively. Findings revealed that the mean crop duration of 340 days were required for one cycle in a year in improved cropping pattern which implied that four crop based cropping pattern was agronomically feasible to replace existing cropping pattern. Total seed/grain yield in terms of REY of improved cropping pattern was 14.85 t ha-1 year-1 which was 44% higher than that of existing pattern (10.30 t ha-1 year-1). Mean production efficiency (35.78 kg ha-1 day-1), land use efficiency (93.15%) and labour employment (589 mandays ha-1 year-1) of improved cropping pattern was 51%, 16% and 62%, higher, respectively than that of existing cropping pattern. The mean net economic advangaes of improved cropping pattern was Tk 12677 ha-1 year-1 which implied that the improved cropping pattern was economically viable. Moreover, the improved cropping pattern increased cropping intensity, farmers knowledge, skill, and income as well as employment. It also maintained soil health by incorporating mungbean stover and T.Aus rice straw in the soil. Therefore, farmers in Kushtia region of Bangladesh could follow the improved cropping pattern in their high and medium high land for higher productivity and profitability as well as employment generation over existing cropping pattern. Bangladesh J. Agril. Res. 43(4): 587-598, December 2018